2016
DOI: 10.31389/eco.81
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Saving Rates: Microdata Evidence from Seventeen Latin American and Caribbean Countries

Abstract: Using microdata on expenditure and income for seventeen Latin American and Caribbean countries, this paper presents stylized facts on saving behavior by age, education, income, and place of residence. Counterfactual saving rates are computed by imposing the saving behavior, the population distribution, or the income distribution of two benchmark economies (the United States and Korea). The results suggest that the difference in national saving rates b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Gandelman (2016) analyzed micro data on expenditure and income for 16 Latin American and Caribbean countries and reported stylized facts of saving behavior by age, education, income and place of residence. Using the United States and Korea as benchmark economies, Gandelman (2016) found that differences in national saving rates between Latin American and Caribbean countries and benchmark economies can mainly be attributed to differences in saving behavior across demographic groups, and to a lesser extent to differences in population distribution by education levels. Other demographic or income distribution differences are not quantitatively important as explanations of differences in aggregate saving rates.…”
Section: Introductionmentioning
confidence: 99%
“…Gandelman (2016) analyzed micro data on expenditure and income for 16 Latin American and Caribbean countries and reported stylized facts of saving behavior by age, education, income and place of residence. Using the United States and Korea as benchmark economies, Gandelman (2016) found that differences in national saving rates between Latin American and Caribbean countries and benchmark economies can mainly be attributed to differences in saving behavior across demographic groups, and to a lesser extent to differences in population distribution by education levels. Other demographic or income distribution differences are not quantitatively important as explanations of differences in aggregate saving rates.…”
Section: Introductionmentioning
confidence: 99%